KERAGAMAN DAN KARAKTERISASI MIKROALGA DARI SUMBER AIR PANAS CIWALINI YANG BERPOTENSI SEBAGAI SUMBER BIODISEL - Gunawan Gunawan (Universitas Lambung Mangkurat, 2010)
The objectives of the research were to obtain specific microalgae that are able to produce high lipid, and to determine suitable culture technique for optimum growth and maximum lipid production. Microalgae were identified, isolated, selected and then grown on IMK medium at 27-29oC under continuous light irradiation for 24 hours. The microalgae were then selected for lipid content using Nile Red. The selected microalgae were then grown under the same medium and condition as before followed by selection based on their growth rate. To find an appropriate medium for specific microalgae, the selected microalgae were then grown on various media such as BG11, Zarrouk, MBM, PHM and BBM media. When a medium was selected, it was then used as the medium for the nitrogen source and light intensity experiments. Those selected microalgae from each location were cultured on the selected medium at different nitrogen concentration (0,5, 1 and 2 M) and different light intensities (35, 70 and 140 µmol photon/m2/sec). The result showed that Ciwalini has diversity index (H) 2,21. Identification indicated that ciwalini species was Chlorophyta. In this research maximum growth rate was at 2 M nitrogen consentratiom with 140 µmol photon/m2/sec light intensity. Lipid content ranged from 11,7% - 28%. The highest lipid content was occurred on media 0,5 M nitrogen consentration and 140 µmol photon/m2/sec light intensity. Lipid Productivity ranged from 0,070,18 g/l/day.